2010
DOI: 10.1007/s11746-009-1538-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aegean Olive Oils by Their Minor Compounds

Abstract: This study presents a combined approach of establishing cultivar differences between Aegean olive oils, obtained from economically important olive oil producing cultivars (cv. Ayvalik and Memecik), based on chemometric evaluation of their content and in particular composition of the minor compounds. Evaluation of minor compounds with principal component analysis and linear discriminant analysis (LDA) indicated differentiation according to the cultivars. LDA produced a 100% correct group classification. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
33
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 25 publications
12
33
2
3
Order By: Relevance
“…Following an investigation comprising four successive crop seasons, Romero et al (2003) concluded that phenolic profiles were mainly influenced by cumulative rainfall. Similarly, Ilyasoglu et al (2010) found that the total phenolic contents of some Aegean VOO-s are greater in the drought than in the rainy crop year, but their observed range of variation is much smaller than that observed in this study. It seems that the total phenolic content could depend less on the plantation area but is much more characteristic of the cultivar and strongly depends on the climate characteristics of the year (see also the above mentioned case of Leccino).…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Following an investigation comprising four successive crop seasons, Romero et al (2003) concluded that phenolic profiles were mainly influenced by cumulative rainfall. Similarly, Ilyasoglu et al (2010) found that the total phenolic contents of some Aegean VOO-s are greater in the drought than in the rainy crop year, but their observed range of variation is much smaller than that observed in this study. It seems that the total phenolic content could depend less on the plantation area but is much more characteristic of the cultivar and strongly depends on the climate characteristics of the year (see also the above mentioned case of Leccino).…”
Section: Resultscontrasting
confidence: 69%
“…The concentrations of the complex phenolic compound oleuropein are in the range of 1.5 and 4 mg·kg −1 and could be similar, for example, to those reported by O. Garcia-Martinez et al (2014a), for the Sicilian varieties Biancolilla, Passulunara, Tonda iblea etc., or Ilyasoglu et al (2010), for the Turkish variety Ayvalik.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement, Dabbou et al (2009) attribute variations of phenolic profile of Tunisian EVOO to the geographic area characteristics, particularly to altitude. Furthermore, scientific data have shown that water status also influence the phenolic profile of the olive oils, but the effect may differ depending on the compounds, since the enzymes involved in the biosynthetic pathway of phenolic compounds are affected by water stress conditions in a different way (Ilyasoglu et al, 2010;Stefanoudaki et al, 2009). Thus, correlations between climatic conditions and minor olive oil compounds may be explained Symbols indicate significant correlations (* P < 0.05, ** P < 0.01).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…In most studies on Turkish olive oil for instance, the main focus was the olive oil from North Aegean (Andjelkovic et al, 2009;Ilyasoglu et al, 2010), the western and south eastern regions of Turkey (Ocakoglu et al, 2009), despite the fact that there are five more distinct olive growing regions in Turkey: The Aegean region (western Turkey), the Marmara region (north-western Turkey), the Mediterranean region (southern Turkey), the Southeast Anatolian region, and the Black Sea region (northern Turkey), listed from the highest percentage production to the lowest one (Arslan and Schreiner, 2012). In contributing to the Turkish olive oil analysis, Andjelkovic et al (2009) analyzed only ten commercial olive oils from North Aegean of Turkey by gas chromatography (GC) while Ilyasoglu et al (2010) applied liquid chromatography-mass spectrometry (LC-MS) to analyzing only thirteen samples from the same region. In the present work, the number of samples is higher, and there are samples from three additional countries.…”
Section: Introductionmentioning
confidence: 99%